Local Determinants of Foreign Direct Investment in Poland - Jaroslaw Michal Nazarczuk; Anna Krajewska (Institute of Economic Research (IER), 2017)
The internationalisation of economies, which foreign direct investments significantly contribute to, affects the growth of regional and local economies. Their choice of location is the topic of frequent debates among scholars, politicians and regional/local authorities. Given the scarcity of empirical evidence on the locational determinants of foreign direct investments at the local level of analysis (LAU 1) in Poland, and the time that has passed since similar analyses were run on a regional scale, we conduct a study investigating the locational determinants of FDIs in Poland between 2011 and 2015.We use a unique dataset comprising data available in public statistics and information gathered from computations run using GIS software indicating the average distances of districts to selected points of interest (such as the border, motorway/express road, airport, railway line, special economic zone, etc.). The utilisation of GIS-based data is a significant improvement to the past research, which tended to use dummy variables in this regard. To identify the key locational determinants, we run a series of negative binomial regressions, due to the count character of the dependent variable.The results prove that a significant part of the spatial distribution of FDIs in Poland can be attributed to factors originating from New Economic Geography, whereas the rest stems from the heterogeneity of local areas. The lower and more detailed scale of the analysis brings to light new facts on the choice of location as compared to previous studies, especially regarding the role of SEZs or proximity to agglomerations.
Keywords: F23; F23; R12; 330; foreign direct investments (FDIs); location determinants; regional and spatial distribution of FDI; LAU 1; Poland